2015
DOI: 10.1073/pnas.1521002112
|View full text |Cite
|
Sign up to set email alerts
|

Constant mortality and fertility over age inHydra

Abstract: Senescence, the increase in mortality and decline in fertility with age after maturity, was thought to be inevitable for all multicellular species capable of repeated breeding. Recent theoretical advances and compilations of data suggest that mortality and fertility trajectories can go up or down, or remain constant with age, but the data are scanty and problematic. Here, we present compelling evidence for constant age-specific death and reproduction rates in Hydra, a basal metazoan, in a set of experiments co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 58 publications
0
85
1
4
Order By: Relevance
“…When this occurs, death is usually preceded by functional Hydra (Martinez, 1998;Schaible et al, 2015), although similar demographic data have been reported for other species (Finch, 2009;Jones et al, 2014). The classical definition of ageing applies most readily to species where the individual is easily defined, and much of the current uncertainty about ageing in corals derives from questions about the nature of the individual.…”
Section: Introductionmentioning
confidence: 66%
“…When this occurs, death is usually preceded by functional Hydra (Martinez, 1998;Schaible et al, 2015), although similar demographic data have been reported for other species (Finch, 2009;Jones et al, 2014). The classical definition of ageing applies most readily to species where the individual is easily defined, and much of the current uncertainty about ageing in corals derives from questions about the nature of the individual.…”
Section: Introductionmentioning
confidence: 66%
“…The lack of a clearly increasing mortality rate with advancing age and the age‐independent regeneration capacity of M. lignano reminds of Hydra , which is shown to be practically immortal (Martínez, 1998; Schaible et al., 2015). As Hydra , flatworms possess stem cells, including a pluripotent subpopulation (Hobmayer et al., 2012; Wagner, Wang & Reddien, 2014), which can replace damaged and old cells and therefore attenuate aging.…”
Section: Discussionmentioning
confidence: 99%
“…Studying species with aging profiles different from those of the established aging models, such as Caenorhabditis elegans , Drosophila melanogaster , and mice, offers insight into naturally occurring mechanisms to delay or suppress senescence and age‐related phenotypes. Particularly interesting are the few animals which are claimed to be immortal, such as Hydra , for which compelling evidence of a nonsenescent life trajectory exists (Martínez, 1998; Schaible et al., 2015) and certain flatworms (Haranghy & Balázs, 1964; Lange, 1968; Tan et al., 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Though ageing is a widespread phenomenon in biology, it is by no means universal: lobsters [13] and hydra [14] show no loss of tissue integrity or reproductive capacity with increasing chronological time, while the North Atlantic Quahog (a hard shelled clam) can live to at least 400 years with no obvious signs of 'ageing' [15]. Salamanders retain regenerative capacity over long periods of chronological time [16] and acute cell senescence is required during regeneration [17]; it is possible that senescence may initially have arisen as a developmental and/or wound healing mechanism that has only recently in evolutionary time been co-opted as a tumour suppressor mechanism with ageing as a side-effect [18].…”
Section: What Constitutes a Good Ageing Model?mentioning
confidence: 99%